Dynamic and adaptive access control model - Guo-zhen SHI; Hao-jie WANG; Yun-fei CI; Si-shui YE; Yun-chuan GUO (Tongxin xuebao)
With the development of cloud computing technology, smart city and mobile office and emergence of mobile smart devices, the resources' environment is increasing complex. The traditional access control model has been difficult to meet the diverse access control requirements and the dynamic and adaptive access control policy. A dynamic and adap-tive access control model combining the resource life cycle management based on ABAC was proposed. The model fo-cused on resource life cycle management considering the relevance of the resource life cycle management and access control policy. In this model, the policy can be changed as the resource life cycle states' change, so the applicability has been improved. In addition, the user access behavior history management function was added in this model, which can adapt the environment better by considering history of user access behavior. At last, the model in general and cloud com-puting access control system was implemented and verified.